Methods of Developing Musical Thinking in Higher Education Students through Music Culture Lessons - Yuldashev Bobirjon Xaydarovich (Research Parks Publishing LLC, 2021)
Music education is a tool that leads a person to beauty, it shapes a person's aesthetic and emotional qualities. Human life is unimaginable without the art of music. Art not only nourishes people spiritually, but also plays an important role in their mental development. The art of music is a powerful tool for learning about life and educating people. This article describes the methods of developing musical thinking for higher education students through music culture lessons.